The Effect Of Early Mobilization Of Post-Section Caesarean Mothers On Pain Intensity At The Aceh Government Mom And Child Hospital, Banda Aceh City - chairunnisa; Mahruri Saputra; Gadis Halizasia; Ferdi Riansyah; Nelva Riza (Teewan Solutions, 2024)
Childbirth can produce pain in post-cesarean section patients which can affect the healing process and slow down the patient's movement due to the pain, so in this study the problem obtained is the intensity of pain in post-cesarean section patients. This study aims to determine the effect of early mobilization in post-cesarean section mothers on pain intensity at the Aceh Government Mother and Child Hospital in Banda Aceh City. This study uses a quantitative research method with a quasi-experimental design with a sample of 30 people who became the intervention group. The intervention group received early mobilization intervention after post-cesarean section. The pain intensity in post-cesarean section patients was measured using a pain measurement scale, namely the Numeric Rating Scale (NRS) and using an early mobilization SOP to be taught to patients and implemented independently. Based on this study, the average pain intensity before early mobilization was 4.06, while the average pain intensity after early mobilization was 2.86, so the results of this study indicate that there is an effect of early mobilization on pain intensity in post-cesarean section mothers which is significant P = 0.000 <0.05. This study concludes that early mobilization can be used as a nursing intervention to reduce pain in post-cesarean section patients. For nursing practitioners, the results of this study can be used as a reference for developing more effective nursing interventions to reduce pain in post-cesarean section patients. Furthermore, this study is expected to serve as a reference and education for patients and their families, the Aceh Government Maternity and Child Hospital in Banda Aceh City, Bina Bangsa Getsempena University, and for future researchers. Keywords: Early Mobilization, Post-Section Caesarean, Pain Intensity.